A comparative review of the effects of different fibre concentrations on arrowroot fibre and other fibre-reinforced composite films. (2023) - Tarique, J.; Sapuan, S.M.; Zainudin, E.S.; Khalina, A.; Ilyas, R.A.; Hazrati, K.Z.; Aliyu, I.
Abstract: In recent years, there has been an increase in the development of composites reinforced with materials derived from renewable resources. Renewable resources are suitable materials for replacing synthetic compounds. The use of natural fibres as reinforcement during the production of starch-based composites is an effective method for improving the functional properties of composite films. This review has therefore been undertaken, focusing on more recent natural fibres-based composite films such as arrowroot fibre, Dioscorea hispida, corn husk, cassava bagasse, sugar palm, and kenaf fibre. The reinforcement of thermoplastic starch by different fibre concentrations improves the mechanical properties and promotes the suitability of starch-based composites as eco-friendly materials.